2009
DOI: 10.3900/fpj.8.5.315.p
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos níveis de atividade física, autonomia funcional e qualidade de vida de idosas integrantes do programa de saúde da família

Abstract: Alencar NA, Bezerra JCP, Dantas EHM. Avaliação dos níveis de atividade física, autonomia funcional e qualidade de vida de idosas integrantes do programa de saúde da família. Fit Perf J. 2009 set-out;8(5):315-21. RESUMOIntrodução: O objetivo do presente estudo foi descrever os níveis de atividade física, autonomia funcional e qualidade de vida em idosas. Materiais e Métodos: A amostra foi constituída de 15 mulheres, com idade entre 60 e 87 anos (67,8±6,9). Os protocolos utilizados foram: (a) nível de atividade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
36

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 25 publications
0
3
0
36
Order By: Relevance
“…That intervention program had the same frequency and duration used in the present study. The initial AI of the present study described the group as weak, similar to the group studied by Alencar et al 38 These authors, 38 with a sample of 15 elderly women, observed that the indicators of autonomy to perform daily life activities by the GDLAM protocol achieved unsatisfactory rates, reinforcing the premise that aging associated with a sedentary lifestyle causes reduced functional capacity. Initially, the HG of the present study was sedentary and, after the intervention, the same group was qualified as good.…”
Section: Discussionmentioning
confidence: 48%
“…That intervention program had the same frequency and duration used in the present study. The initial AI of the present study described the group as weak, similar to the group studied by Alencar et al 38 These authors, 38 with a sample of 15 elderly women, observed that the indicators of autonomy to perform daily life activities by the GDLAM protocol achieved unsatisfactory rates, reinforcing the premise that aging associated with a sedentary lifestyle causes reduced functional capacity. Initially, the HG of the present study was sedentary and, after the intervention, the same group was qualified as good.…”
Section: Discussionmentioning
confidence: 48%
“…The questionnaire was conducted by previously trained evaluators in order to reduce variability among evaluators. The instrument had satisfactory validity when compared with other methods of measuring physical activity, 22 such as the Bouchard Record (a subjective measure), with a correlation of r=0.78, and the pedometer (objective measure), with a correlation of r=0.72. Reproducibility in elderly subjects was r=0.89.…”
Section: Practice Of Regular Physical Exercise -Prementioning
confidence: 94%
“…Aging is a complex process, inherent to all the structures of the organism. Over time, the tissues start to be worn out and thus compromising the organs and their functions (Alencar, Bezerra, & Dantas, 2009). The compromise of the body structures facilitates risks for falls.…”
Section: Incident Of Femoral Fracture and Screening Of Signs Of Deprementioning
confidence: 99%